(untitled) (Iraqi Journal of Science, 2023)
Measuring goat weight on a farm is carried out by two methods. The first method conventionally measures the chest girth (CG) and body length (BL), while the second is performed using a scale. This study aimed to facilitate the CG and BL measurements to estimate goat weight more efficiently through image processing. The endpoints of CG and BL were determined automatically using binary large object (BLOB) segmentation. The images of 120 goats were taken at three different shooting distances of 50 cm, 70 cm, and 90 cm. The statistical testing of the three scenarios in this study explained that the ideal distance to take pictures is the basis for determining whether or not the size of the circumference and BL is appropriate as a feature for estimating the weight of goats based on image processing. Statistical analysis showed that the features of CG and BL at a distance of 50 cm and 70 cm were not significantly different from the measurements of CG and BL of goats carried out directly (actual data). In comparison, the results of testing the feature prediction data at a distance of 90 cm are significantly different from the actual data.